Changes in expression of NLRP3 inflamasome and IL-1β in the development of oxazolone-induced colitis in rats and on the background of administration of simvastatin and interleukin-1β receptor antagonist - O. S. Zherebiatiev; N. M. Polishchuk (Zaporozhye State Medical University, 2021)
The aim. To study the expression of mRNA of the NLRP3 inflammasome and proinflammatory cytokine IL-1β in the inflamed colon of rats with experimental oxazolone-induced colitis and against the background of the introduction of simvastatin and antagonist of interleukin-1 receptors. Materials and methods. Experiments were carried out on male Wistar rats aged 8 months (body mass 120-150 g). Tissue samples were obtained from rats with experimental oxazolone-induced colitis (n = 20), rats with oxazolone-induced colitis treated with simvastatin (n = 20); rats with oxazolone-induced colitis treated with interleukin-1 receptor antagonist (n = 20) and control animals (n = 10). Clinical signs of colitis were evaluated by the clinical index of disease activity on the following parameters: weight loss, stool consistency and animal behavior. For macroscopic assessment of the development of colitis areas of inflammation and ulceration were investigated. For histological evaluation of lesions, sections of the intestine were stained with hematoxylin and eosin and cellular inflammatory infiltrates, epithelial hyperplasia, ulceration and loss of intestinal glands were studied. IL-1β and NLRP3 inflammasome mRNA expression was analyzed by real-time reverse transcriptase-polymerase chain reaction. Results. Animals treated with oxazolone rapidly developed colitis marked by weight loss and diarrhea peaking by day 2 after oxazolone administration and leading to death of 40 % of the rats by day 4. The histological observation showed inflammatory cell infiltration, including polymorphonuclear leukocytes and multiple erosive lesions in the large intestine. We determined that the expression level of the proinflammatory cytokine IL-1β is increased in colon samples of rats with oxazolone-induced colitis. IL-1β expression is increased 3.5‐fold in inflamed colon compared to uninflamed tissue. Administration of simvastatin and an interleukin-1 receptor antagonist to rats with oxazolone-induced colitis resulted in a 30 % and 2-fold decrease expression of IL-1β in colon samples. In addition, we examined NLRP3 expression in these tissues. RT‐PCR analysis demonstrates a 71‐fold increased expression of NLRP3 mRNA expression in colon samples tested. Administration of simvastatin and an interleukin-1 receptor antagonist to rats with oxazolone-induced colitis resulted in a 2.5- to 3.0-fold decrease expression of NLRP3 mRNA in colon samples. Conclusions. IL-1β and NLRP3 mRNA expression levels were elevated in the inflamed colon of rats with experimental oxazolone-induced colitis. Administration of simvastatin and an interleukin-1 receptor antagonist against the background of colitis caused a decrease in the expression levels of IL-1β and NLRP3 mRNA in the tissues of the intestine. Detection of abnormal expression of IL-1β and NLRP3 mRNA could provide insights into pathogenesis of Crohn's disease, and may help to identify future potential targets for therapeutic strategies in people with inflammatory bowel disease.